Bellagio report on Healthy agriculture, healthy nutrition, healthy people⋆ - Simopoulos Artemis P.; Bourne Peter G.; Faergeman Ole (Oilseeds and fats, crops and lipids, 2013)
The Bellagio Report on Healthy agriculture, healthy nutrition, healthy people is the result of the meeting held at the Rockefeller Foundation Bellagio Center in Lake Como, Italy, 29 October–2 November 2012. The meeting was science-based but policy-oriented. The role and amount of healthy and unhealthy fats, with attention to the relative content of omega-3 and omega-6 fatty acids, sugar, and particularly fructose in foods that may underlie the epidemics of non-communicable diseases (NCD’s) worldwide were extensively discussed. The report concludes that sugar consumption, especially in the form of high energy fructose in soft drinks, poses a major and insidious health threat, especially in children, and most diets, although with regional differences, are deficient in omega-3 fatty acids and too high in omega-6 fatty acids. Gene-nutrient interactions in growth and development and in disease prevention are fundamental to health, therefore regional Centers on Genetics, Nutrition and Fitness for Health should be established worldwide. Heads of state and government must elevate, as a matter of urgency, Nutrition as a national priority, that access to a healthy diet should be considered a human right and that the lead responsibility for Nutrition should be placed in Ministries of Health rather than agriculture so that the health requirements drive agricultural priorities, not vice versa. Nutritional security should be given the same priority as food security.